Challenges for a changing world - Shultz, George; Ford, Gerald; Chaves, Aureliano; Galves, Ernane; Ledoux, Pierre; Colin, Oswaldo; Garnero, Mario; Simon, William (Sao Paulo, Brasil Forum Das Americas)
This volume comprise of speeches and talks given during the annual gathering of the Brasilinvest which coincided with the meetings of the International Monetary Fund.
lje 18/10/18
Loans
Keywords: Economic development; Economic history; Economic conditions-Brazil; Brazil